Effect of tube inclination angle on the thermal and fluid dynamic performance of flat tube heat exchanger - Ahmed Yousif Adam, Mohammed (2017)
At the present time, the performance of finned and flat tube heat exchangers (HEs) has become a very important issue in the thermal industrial sector. Finned-and-flat tube heat exchangers have gained great interest from many researchers due to their role in any thermal engineering system. Some geometrical and process parameters such as fin spacing, tube spacing, tube inclination angle, etc. affects the performance of fin-and flat tube heat exchangers. Significant number of research have been done to study the effect of such geometrical and process parameters. However, the effect of flat tube inclination angle on the thermal-hydraulic performance of fin-and-tube HE is not fully examined. Thus, the aim of this study was to investigate the effect of flat tube inclination angle, air velocity and tube configuration on the thermal and flow characteristics of compact fin-and-flat tube heat exchangers. A series of experimental and numerical investigations were carried out to evaluate the influence of the aforementioned parameters on the thermal-hydraulic performance between the tube bundles. Moreover, Response Surface Methodology (RSM) was used to determine the optimum parameter condition for the fin-and–tube HE. The range of the parameters considered in the study were tube inclination angle from 0˚ to 150˚, inlet air flow velocity from 1.8 to 3.8 m/s and tube configuration (inline and staggered). For the experiments, the wind tunnel available at the Faculty of Mechanical Engineering, UMP was used. The wind tunnel was equipped with a blower of capacity 50 W, flow straightener, test section and measuring sensors. Twelve plate fin and nine flat tube heat exchangers test sections were designed and manufactured at various inclination angles and configurations. Temperature, velocity, and pressure measurements were recorded at various positions in the test section as well as before and after the test section. For the numerical analysis, the CFD commercial software called ANSYS FLUENT-15 was used to solve the Navier-Stoke and energy equations together with proper turbulent equations. The parameters are similar to the experimental investigation. The experiment and numerical analysis used Nusselt number, pressure drop, and area goodness factor to evaluate the thermal-hydraulic performance of fin-and-flat tube heat exchangers. The major findings showed that flat tube inclination angle has significant impact on the heat transfer enhancement. However, the results from both experimental and numerical analysis revealed that increasing the tube inclination angle from 0˚ to 90˚ augments the convective heat transfer coefficient. While 120˚ and 150˚ provide thermal performance close to 60˚ and 30˚, respectively. The average deviations of Nusselt number between experimental and numerical results were 5.42% and 4.44% for inline and staggered configurations respectively. Moreover, due to the air flow blockage caused by inclining the tube angle, the pressure drop increases dramatically for all cases studied. From all acquired results, the best thermal performance occurred at 0˚, while 90˚ provided the minimum thermal performance. Therefore, inclining the tube is beneficial for enhancing the heat transfer performance but is not beneficial in term of pressure drop as it requires higher pumping power. The developed correlations from the RSM can predict experimental data with average deviation of 2.78% for Nu for both configurations. Moreover, it can predict the numerical data with average deviation of 0.554% and 0.92% for inline and staggered configuration, respectively. The optimum parameters are found to be with high air velocity and low tube inclination angle which provide maximum heat transfer enhancement and low-pressure drop penalty. Thus, it is recommended for the design of fin-and-flat tube HEs.